Association of Immune Thrombocytopenia and T-Lymphoblastic Lymphoma in a Pediatric Patient - Denu, Ryan A.; Matson, Daniel R.; Davis, Matthew J.; Tedford, Natalie J.; Brichta, Christine E.; Diamond, Carol A.; Hoover-Regan, Margo L. (Case Reports in Hematology, 2019)
Immune thrombocytopenia (ITP) is characterized by isolated thrombocytopenia of unclear etiology. We present a unique case of an 8-year-old girl with chronic ITP who was subsequently diagnosed with T-lymphoblastic lymphoma at age 11. The clinical course was complicated by the occurrence of nonepileptiform events with bizarre behavior changes following the administration of nelarabine and intrathecal and high-dose systemic methotrexate. This case highlights an unusual co-occurrence of hematologic malignancy and chronic ITP in an otherwise healthy child. We speculate that underlying genetic or immunologic lesions may predispose a subset of pediatric ITP patients to the development of hematologic malignancies.